#1**+2 **

We have that

4(9) + b = 7b + 0 simplify

36 + b = 7b subtract b from both sides

36 = 6b divide both sidesby 6

6 = b

4((9) + 6 = 7(6) + 0

36 + 6 = 42

So.....n = 42

CPhill Apr 7, 2020

#2**+2 **

If the triangle is x, then 4x base nine is equal to 36+x base 10 and x0 base 7 is equal to 7x base 10. Since they are equal that means tha36+x=7x, solving for x, we get x= 6. If the triangle is 6, we get 46 base 9 equals 60 base severn which equals **42 base 10** which is your answer.

Hope it helps!

HELPMEEEEEEEEEEEEE Apr 7, 2020